Increasing the growth and yield of tomato plants (Lycopersicum Esculentum Mill) by Applying Palm Oil Compost - Lufita Nur Alfiah; Khusnu Abdilah Siregar; Eko Novianto (LPPM UNIVERSITAS ISLAM KUANTAN SINGINGI, 2023)
Tomato (Lycopersicum esculentum Mill) is a horticultural commodity classified as a vegetable plant and has high economic value in the local and international markets. This research was conducted to determine the effect of applying oil palm frond compost on the growth and yield of tomato plants and to determine the best dosage of oil palm frond compost to increase the yield and growth of tomato plants. This research was conducted at the Screen House of the Faculty of Agriculture, University of Pasir Pengaraian, from July 2022 to October 2022. The design used in this study was a Completely Randomized Design (CRD) with 5 treatments, namely P0 = Without adding oil palm. frond compost, P1 = 25 g/polybag of palm frond compost, P2 = 50 g/polybag of palm frond compost, P3 = 75 g/polybag of palm frond compost, P4 = 100 g/polybag of palm frond compost. The results showed that the application of various doses of palm frond compost significantly affected the parameters of the number of fruits per tomato plant. Still, they had no significant effect on the parameters of plant height, number of leaves, and flowering time. The P4 treatment, namely applying palm frond compost at a dose of 100 g/polybag, tended to produce the best observation parameter: the number of fruits per plant. In contrast, the plant height parameter tended to be better with applying palm fronds. frond compost.